2020
DOI: 10.1097/mpg.0000000000003024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Depression and Anxiety in a Cohort of Adolescents With Nonalcoholic Fatty Liver Disease

Abstract: Objectives: To determine the incidence of clinically diagnosed depression and anxiety in adolescents with nonalcoholic fatty liver disease (NAFLD). Methods: This was a prospective, longitudinal cohort study between January 1, 2012 and July 1, 2018 conducted in a Children's Hospital Pediatric Gastroenterology Clinic. Participants included adolescents 12 to 17 years old at baseline with biopsy-confirmed NAFLD. The primary outcomes were having depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In a longitudinal cohort study of 160 adolescents with biopsy-proven NAFLD, Noon et al demonstrated that the mental health burden adolescents with NAFLD face is substantial. 33 Over a 4 year average following diagnosis with NAFLD, 1 in 6 adolescents with NAFLD developed clinically relevant depression. Notably, adolescents with NAFLD whose liver chemistry worsened over time were more likely to develop depression.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In a longitudinal cohort study of 160 adolescents with biopsy-proven NAFLD, Noon et al demonstrated that the mental health burden adolescents with NAFLD face is substantial. 33 Over a 4 year average following diagnosis with NAFLD, 1 in 6 adolescents with NAFLD developed clinically relevant depression. Notably, adolescents with NAFLD whose liver chemistry worsened over time were more likely to develop depression.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In the cohort by Cho et al, obese people with greater severity of depression exhibited an increased risk of having NASH with greater degrees of fibrosis when compared to obese people having lesser to no depression (aH R = 3.55, 95% CI: 1.38–9.13, p < 0.005) 14 . Similarly, in the second longitudinal study, adolescents who developed depression reported worse outcomes based on alanine transferase liver enzyme serology (indicator of liver injury) when compared with those who did not develop depression (i.e., improved 21%, stable 36%, worse 43% versus improved 42%, stable 35%, worse 23%; p < 0.01, respectively) 15 …”
Section: Association Of Nafld With Psychiatric Disordersmentioning
confidence: 81%
“…Another longitudinal study that followed adolescents ( n = 160) with NAFLD for a mean duration of 3.8 years reported a steady increase in the incidence of depression among participants over time from baseline (i.e., 8.1% had depression initially) 15 . During the follow-up period, an additional 9.5% (95% CI = 4.7%–14.3%) of the adolescents with NAFLD developed depression.…”
Section: Association Of Nafld With Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that high bilirubin level was associated with depression [ 38 ]. Elevated ALT was found in adolescents with NAFLD who developed depression [ 39 ] and it was also a significant independent predictor for the occurrence of minor and major depression in adults [ 40 ]. Moreover, depression would escalate the histological changes in reverse, probably through the monoamine oxidase-A enzyme pathway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%